A new analgesic agent based on hexaazaisowurzitan: feasibility of using in managing patients with cancer - K. A. Lopatina; S. G. Krylova; E. A. Safonova; E. P. Zueva; D. A. Kulagina; А. A. Churin; T. I. Fomina; S. V. Sysolyatin (Сибирский онкологический журнал)
Purpose: to study gastrotoxic and ulcerogenic effects of a long-term administration of a newly synthesized compound from the hexaazaisowurzitan (thiowurtzine) series in rats, as well as to assess its effect on the transplantable tumor in mice.Material and Methods. Lewis lung carcinoma was transplanted into mice, and thiowurtzine was prescribed for a long course together with cyclophosphamide. In the terminal stage of tumor development the mass of the primary node, the number and area of metastases in the lungs of mice were measured. Histological sections of the stomach were studied in rats after a 90-day administration of thiowurtzine.Results. Thiowurtzine at therapeutic dosages of 50 and 100 mg/kg for a course of 19 days potentiated the effect of cyclophosphamide to inhibit tumor dissemination and exerted a direct antitumor effect in mice with lewis lung carcinoma. A dose of 1000 mg/kg for 90 days did not cause ulcerogenic action of thiowurtzine.Conclusion. The absence of a stimulating effect on tumor growth in animal experiments and intactness in relation to the gastric mucosa during chronic administration of thiowurtzine allow us to recommend this innovative analgesic for clinical study as a concomitant analgesia in cancer patients.